Albumin and Sex Hormone Binding Globulin based Testosterone Indices in Polycystic Ovarian Syndrome - Khan, Sikandar Hayat; Urooj, Uzma; Quereshi, Zeeshan Ali; Sarwar, Urwa; Shahid, Rahat; Noor, Chaudhry Qamar Ul Haq (Pakistan Armed Forces Medical Journal, 2024)
Objective: To evaluate total testosterone, “Free Androgen Index”, calculated free testosterone, % free testosterone, calculated bioavailable testosterone, and % testosterone as a possible biomarker to predict presence of Polycystic ovarian syndrome as per Rotterdam criteria.Study Design:  Comparative cross-sectional study.Place and Duration of Study: Pakistan Naval Hospital, Islamabad Pakistan, from Jan 2018 to Jul 2020.Methodology: A total of 328 female subjects were included in the study, which included 166 subjects with polycystic ovarian syndrome and 162 without polycystic ovarian syndrome as per Rotterdam criteria. Various albumin and sex hormone binding globulin-based androgen measures, including calculated free testosterone and calculated bioavailable testosterone, and only the included measure Free Androgen Index were calculated. These various measures were evaluated between polycystic ovarian syndrome and non-polycystic ovarian syndrome. Following that, receiver operating curve analysis was carried out to see area under curve for various androgen excess parameters to measure the diagnostic performance of each measure for diagnosing polycystic ovarian syndrome.Results: Almost all androgen excess measures demonstrated significant differences between subjects with or without polycystic ovarian syndrome. Area under curve as measured by receiver operator curve analysis shows highest area under curve for as: Bioavailable testosterone =0.792[95% CI: 0.743-0.842], Free testosterone =0.791[95% CI: 0.743-0.842], Free Androgen Index =0.782[95% CI: 0.731-0.833], Total testosterone =0.748[95% CI: 0.696-0.800], %Bioavailable testosterone =0.675[95% CI: 0.619-0.734], % Free testosterone =0.671[95% CI: 0.612-0.729], and Sex Hormone Binding Globulin =0.337[95% CI: 0.0.78-395].Conclusion: Free testosterone followed by Bioavailable testosterone and Free Androgen Index, have demonstrated higher Area Under Curve ....